Some kind of wonderful - Hughes, John; Deutch, Howard; Stoltz, Eric; Masterson, Mary Stuart; Thompson, Lea; Sheffer, Craig (Paramount Pictures, 1987)
Keith (Eric Stolz), a sensitive high school loner, wants more than anything to get the most desired girl in school, Amanda Jones (Lea Thompson) out on a date. His tomboyish best friend Watts (Masterson) loves Keith, but helps him get what he wants.